Inversion phenomena in chiral liquid crystals - Goodby, J. W.; Styring, P.; Slaney, A. J.; Vuijk, J. D.; Patel, J. S.; Loubser, C.; Wessels, P. L. (Ferroelectrics, 1993)
Liquid crystals composed of chiral materials exhibit chiral properties and structures. For instance, cholesteric phases have helical structures and exhibit thermochromic properties, whereas ferroelectric smectic C* phase are also helical and can exhibit thermochromism, but they also possess a spontaneous polarization generated by a reduced space symmetry. Properties such as helicity and the spontaneous polarization are directional and depend upon the molecular asymmetry. In this article we discuss how the directionality of these properties can be affected by changes in temperature, which can produce inversions in helicity and to the direction of the spontaneous polarization.